Pengembangan Fitur Penelitian Tugas Real–Time Pada Sistem E-Learning Berbasis Web Untuk Meningkatkan Interaktivitas Siswa - Majid Armansyah; Adam Sekti (Bulletin of Computer Science Research, 2025)
This research develops a real-time assignment assessment feature in a web-based e-learning system to enhance student interactivity and learning effectiveness. One of the main challenges commonly found in conventional e-learning systems is the delay in the assessment process, which prevents students from receiving timely feedback. This condition negatively affects learning motivation, student engagement, and the speed at which students grasp the material. To address this issue, this study designs and implements a real-time assessment feature using the CodeIgniter framework, HTML, and MySQL with a three-layer architecture. The developed features include automatic assessment, direct feedback, instant notification systems, and an integrated score-monitoring dashboard. The research employs a Research and Development (R&D) method with the Waterfall development model, which consists of requirement analysis, system design, implementation, and testing phases. Data were collected through interviews, observations, and expert validation to ensure the feasibility and appropriateness of the system. The test results indicate that the real-time assessment feature significantly improves teacher efficiency in grading assignments, accelerates the delivery of scores, and increases student motivation during the learning process. Expert validation showed that the system is highly feasible, while user evaluations revealed enhanced interactivity and ease of use. Overall, the implementation of the real-time assessment feature in this web-based e-learning system successfully creates a more responsive, adaptive, and interactive learning environment. This development provides tangible benefits for supporting digital learning processes and serves as a foundation for future feature enhancements in e-learning platforms.